Operational strategy, capabilities, and successfully accomplishing business strategy - Ayman Sadik Al Najjar; Mahmoud Salameh Qandeel (Journal of Applied Research in Technology & Engineering)
This study investigates the vital role of corporations’ operational capabilities, which involve resources, competencies, and processes, in attaining the business’s strategic goals for profitability and sustainability. The methodology employs a selective literature review to analyze case studies, books, and articles that give an overview of operational management and its importance in achieving corporate goals. The results exhibit the challenges posed by rapid market changes, revealing the deficiencies of traditional operational systems focused solely on efficiency and cost. To attain sustained success, manufacturers must focus on a client-valued approach, align objectives with capabilities, and support inter-functional links. Companies with distinctive managerial processes outperform in profitability, emphasizing the significance of investing in management capabilities. Operational excellence necessitates a focus on efficiency, innovation, and customer experience, prompting a shift towards a learning style that encourages innovation. Aligning innovation efforts with business strategy is essential for sustainable competitive advantage. Technological innovation, particularly AI adoption, plays a transformative role in operational innovation, highlighting the importance of dynamic capabilities in managing technological change. Yet, effective inventory and supply chain management are important for meeting customer demand and maximizing efficiency through collaboration and adaptable control.